Determining the Quality of Electric Motors by Vibro-Diagnostic Characteristics - Arhun, Shch.; Migal, V.; Hnatov, A.; Ponikarovska, S.; Hnatova, A.; Novichonok, S. (EAI Endorsed Transactions on Energy Web, 2020)
Experimental studies of vibrations of asynchronous electric motors (EMs) of the electric bus traction electric drive are carried out in the paper. The presented studies are based on generalization of the diagnostic features of vibration characteristics and statistics concerning the limiting values of vibration parameters of EMs and their dependence on the technical condition. The analysis of the obtained results allowed us to determine the permissible vibration levels of EMs in the frequency range from 5 Hz to 10 kHz. The method of diagnosing EMs traction electric drive according to the indicators of vibration levels is developed, which allows to evaluate their technical condition. The values of the permissible vibrational accelerations of the electric bus EMs are determined, which enable to estimate their technical level. This method allowed to develop classes of evaluation of the EMs technical condition by the level of their vibration, which makes possible to predict their resource.